2004
DOI: 10.1007/s00330-004-2492-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiplanar functional imaging of the larynx and hypopharynx with multislice spiral CT

Abstract: The purpose of this study is to evaluate multislice spiral CT (MSCT) in multiplanar functional imaging of the larynx and hypopharynx and to define the optimal image planes for the delineation of the tumor and specific anatomical structures. Forty patients with suspected tumors of the larynx or hypopharynx were examined with MSCT during quiet breathing (QB), E-phonation (EP) and modified Valsalva maneuver (VM). Images were read in the axial, coronal and sagittal planes. Overall image quality, delineation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 28 publications
0
15
0
6
Order By: Relevance
“…Keberle et al 8 found that coronal reformats led to a better visualization of tumor extension in 33% of patients and influenced the treatment decisions in 19% of patients. 8 Lell et al 9 found that CT imaging with the patient phonating correctly identified all of the patients in their study with vocal cord fixation and that E phonation was better than the Valsalva maneuver. Another study by Stadler et al, 10 comparing nonfunctional CT (during quiet breathing) and functional CT (including Valsalva and E-phonation maneuver), reported that functional CT was more accurate than nonfunctional CT for TNM-staging of laryngeal and hypopharyngeal cancers.…”
Section: Discussionmentioning
confidence: 90%
“…Keberle et al 8 found that coronal reformats led to a better visualization of tumor extension in 33% of patients and influenced the treatment decisions in 19% of patients. 8 Lell et al 9 found that CT imaging with the patient phonating correctly identified all of the patients in their study with vocal cord fixation and that E phonation was better than the Valsalva maneuver. Another study by Stadler et al, 10 comparing nonfunctional CT (during quiet breathing) and functional CT (including Valsalva and E-phonation maneuver), reported that functional CT was more accurate than nonfunctional CT for TNM-staging of laryngeal and hypopharyngeal cancers.…”
Section: Discussionmentioning
confidence: 90%
“…Thick slice thickness reduces resolution and makes multi-planar reformation MPR sub-optimal. When overlapping images are reconstructed from raw data with a nominal slice thickness of 0.5-1.25 mm, (MPR) images of the tumor can be viewed interactively in any arbitrarily chosen imaging plane 12 . Due to better delineation of bony extent and lymph node evaluation by contrast enhanced, CT scan (CECT) has become an essential part of the workup of HNCs patients.…”
Section: Resultsmentioning
confidence: 99%
“…Valsalva, modifiye Valsalva manevrası, fonasyon veya inspirasyon sırasında sırasında yapılan ek çekimler mukozal yüzeylerin ve derin yayılımların (paraglottik alandan tiroid kıkırdağa fiksasyon gibi) veya vokal kordun mobilitesinin değerlendirilmesi mümkün olmaktadır (17,18).…”
Section: Bulgularunclassified